‘IMPLEMENTATION OF PUBLIC SERVICES MALL FOR THE COMMUNITY IN PALEMBANG CITY’: ‘PENYELENGGARAAN MALL PELAYANAN PUBLIK UNTUK MASYARAKAT DI KOTA PALEMBANG’ - Aryanisila (Jurnal Administrasi Publik dan Pemerintahan, 2023)
Government efforts to enhance the exceptional of public offerings never prevent, until the promulgation of regulation number 25 of 2009 regarding public services as a milestone in all efforts to boost up the conclusion of top notch public service in Indonesia. one of the breakthroughs and improvements to comprehend splendid provider is the enactment of Permenpan RB number 23 of 2017 concerning the implementation of the general public service Mall (MPP). The implementation of MPP in Palembang is based on Palembang Mayor's law No. fifty four of 2018 regarding Public provider department shops in the city of Padang, led by using the pinnacle of the Padang metropolis One-forestall funding office. The implementation of the public provider mall is aimed toward imparting ease of service to the human beings in the town of Palembang fast and effortlessly in addition to getting facilities and infrastructure which might be handy for the recipient of the carrier. The results showed that, first of all the low first-rate of human resources available at public provider shops, the unavailability of centers and infrastructure that were relaxed for recipients of offerings and the lack of socialization by using the authorities regarding the life of public provider department shops in the metropolis of Palembang.